April D. DeConick , The Gnostic New Age: How a Countercultural Spirituality Revolutionized Religion from Antiquity to Today, Columbia University Press, New York 2016, s. xii i 380. - Koszałka, Łukasz (Studia Gdańskie, 2021)
April D. DeConick , The Gnostic New Age: How a Countercultural Spirituality Revolutionized Religion from Antiquity to Today, Columbia University Press, New York 2016, s. xii i 380.